PENGARUH LINGKUNGAN BELAJAR TERHADAP KARAKTER RELIGIUS SISWA DI SMP IT NURUL FADHILAH - Cyndi Pangolangan Hrp; Abdul Fattah Nasution; Nur Atiah Nasution; Aulia Jannah; Abdul Latif Sitompul (Cendekia Madani Nusantara, 2026)
Education is not solely oriented toward academic achievement but also plays a crucial role in shaping students' character, particularly religious character. Religious character is the primary foundation for developing students with noble morals, integrity, and the ability to practice religious values ​​in their daily lives. One factor influencing the formation of students' religious character is the school environment, including the physical, social, and academic environments. This study aims to determine the influence of the school environment on the religious character of students at SMP IT Nurul Fadhilah. This study used a quantitative approach with descriptive methods. Data collection was conducted through distributing questionnaires using a Likert scale to students as respondents, and documentation served as supporting data. The data obtained were analyzed using descriptive statistics and inferential analysis with the help of the SmartPLS application to examine the relationships and influences between variables. The results of this study are expected to provide an empirical overview of the role of the school environment in shaping students' religious character and serve as evaluation material and a reference for schools in improving the quality of learning environments that support the strengthening of religious character education. Keywords: school environment, religious character, character education, junior high school students